Bone reconstruction after surgical treatment of experimental peri‐implantitis defects at a sandblasted/acid‐etched hydroxyapatite‐coated implant: an experimental study in the dog. (15th October 2015) - Namgoong, Hee; Kim, Myung duck; Ku, Young; Rhyu, In‐Chul; Lee, Yong Moo; Seol, Yang Jo; Gu, Hee jin; Susin, Cristiano; Wikesjö, Ulf ME; Koo, Ki‐Tae
Abstract: Objectives: The objective of this study was to evaluate bone formation/osseointegration following surgical treatment of experimental peri‐implantitis at dental implants with different surface characteristics exposed to ligature‐induced breakdown conditions. Methods: Ten turned (control), 10 sandblasted/acid‐etched (SA), and 10 SA/hydroxyapatite nanocoated (HA) implants were installed into the edentulated posterior mandible in five Beagle dogs and allowed to osseointegrate for 12 weeks. Ligature‐induced breakdown defects were then induced over 23 weeks using stainless steel wire ligatures. The ligatures were removed and soft tissues were allowed to heal for 3 weeks. Next, exposed implant surfaces were decontaminated followed by guided bone regeneration using a collagen membrane and submerged wound healing. The animals were euthanized for histometric analysis at 12 weeks post‐surgery. Results: The radiographic analysis showed vertical bone loss following ligature‐induced breakdown without statistically significant differences among implant technologies. The histometric analysis showed significantly enhanced bone formation (height) at SA and SA/HA compared with turned implants ( p = 0.028) following reconstructive surgery. Bone formation area was greater at SA/HA compared with turned implants, however the difference did not reach statistical significance. Conclusions: While ligature‐induced defect progression does not appear implant surface dependent in this animal model, bone formation at the decontaminated implant surfaces appears more favourable at SA and SA/HA over turned implants following reconstructive surgery.